Heliox breathing equally influences respiratory mechanics and cycling performance in trained males and females - Wilkie, S. S.; Dominelli, P. B.; Sporer, B. C.; Koehle, M. S.; Sheel, A. W. (Journal of Applied Physiology, 2015)
In this study we tested the hypothesis that inspiring a low-density gas mixture (helium-oxygen; HeO2) would minimize mechanical ventilatory constraints and preferentially increase exercise performance in females relative to males. Trained male (n = 11, 31 yr) and female (n = 10, 26 yr) cyclists performed an incremental cycle test to exhaustion to determine maximal aerobic capacity (VO2max; male = 61, female = 56 ml/kg·min). A randomized, single-blinded crossover design was used for two experimental days where subjects completed a 5-km cycling time trial breathing humidified compressed room air or HeO2 (21% O2:balance He). Subjects were instrumented with an esophageal balloon for the assessment of respiratory mechanics. During the time trial, we assessed the ability of HeO2 to alleviate mechanical ventilatory constraints in three ways: 1) expiratory flow limitation, 2) utilization of ventilatory capacity, and 3) the work of breathing. We found that HeO2 significantly reduced the work of breathing, increased the size of the maximal flow-volume envelope, and reduced the fractional utilization of the maximal ventilatory capacity equally between men and women. The primary finding of this study was that inspiring HeO2 was associated with a statistically significant performance improvement of 0.7% (3.2 s) for males and 1.5% (8.1 s) for females (P < 0.05); however, there were no sex differences with respect to improvement in time trial performance (P > 0.05). Our results suggest that the extent of sex-based differences in airway anatomy, work of breathing, and expiratory flow limitation is not great enough to differentially affect whole body exercise performance.